Fructose-maltodextrin ratio governs exogenous and other CHO oxidation and performance - O'Brien, W.; Stannard, S. R.; Clarke, J.; Rowlands, D. S. (Medicine & Science in Sports & Exercise, 2013)
Introduction: Fructose coingested with glucose in carbohydrate (CHO) drinks increases exogenous-CHO oxidation, gut comfort, and physical performance.